Electrospray-mass spectrometric studies of selectivity of alkali metal cations extraction by calix[4]arene crowns. Issue 3 (2000) - Allain Allain, F. F.; Virelizier Virelizier, H. H.; Moulin Moulin, C. C.; Jankowski Jankowski, C. K. C. K.; Dozol Dozol, J. F. J. F.; Tabet Tabet, J. C. J. C.
Abstract : Electrospray Ionization Mass Spectrometry (ESI/MS) has quickly become a versatile method of qualitative analysis of a wide variety of host–guest complexes formed in solution. However, considerable controversy exists on how ESI spectra quantitatively reflect and compare to the results obtained on these complexes. The extraction of alkali cations from acidic aqueous solutions by nine various calix[4]arenes-crown-6 diluted in NPOE, was studied by using ESI/MS. The stoichiometry of cesium complex and Cs + /Na + selectivity were evaluated.